Hydrochemistry of Mountainous Rivers (Sierras de Córdoba, Argentina): dissolved major elements. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Sierras Pampeanas of Córdoba, Argentina, is an interesting locality to study the geochemistry of mountainous river systems, both for their socio- economic and cultural significance and for the diversity of streams and rivers that drain its slopes. Several important drainage networks in Córdoba Province have their headwaters in these ranges. In this work, the major chemical composition of water collected from four hydrological catchments is analyzed, with the aim of determining the sources of solutes, the geochemical processes that control their basin’s dynamics and the influence of climatic conditions on the seasonal variation of elemental concentrations. Four drainage basins were selected for this study. All basins are classified as 5th order in Horton’s classification (1945) (modified by Stralher, 1987) and their mean slopes vary between ~5%, in the eastern flank, and more than 9% on the range’s western side. The study area is located between 31° 30’ - 32° 00’S and between 64° 30’ and 65° 10’W. Maximum altitude is about 2,400 m a.s.l. (Fig. 1). Dominant rocks are granitoids of the Achala Batholith that crop out in the upper and middle parts of the study basins, while gneisses and modern sediments dominate in the lower reaches. Climate is semiarid; mean rainfall reaches about 750 mm per year. The atmospheric input chemical signature (plu- vial and snow precipitation) was analyzed and compared with that of springs and 1st order streams (Fig. 3) using an upper continental crust (UCC, McLennan, 2001) normalized diagram. The concentration of dissolved major and trace elements is of the order of 103 to 107 times lower than the mean Upper Continental Crust. According to the observed patterns, atmospheric and spring chemical signals are very similar; however, elements such as Si, Na+ and in less importance Al+3 and Mg+2 are more enriched in springs and 1st order streams than in precipitations. The latter suggests an important contribution to water discharges in these small hydrological systems from rain/snow water stored in fractures and pores where long residence time allows silicate hydrolysis and the consequent release of more insoluble elements to the water, such as Al+3. Decreasing concentration of K+ in springs and streams is likely due to its incorporation into the illite lattice. Dissolved Ca2+ is the only major cation that keeps the atmospheric signal. In figure 4 river samples were divided according to their Horton’s order and the major ionic composition was normalized to the corresponding average values in the precipitation. As seen in the diagram, all patterns show the same trend and, as usual, elemental concentrations increase in the flow direction, evidencing solute contribution by mineral weathering. Most elements are more concentrated in superficial waters with the exception of K+, which remains associated to clay minerals, and Cl-, whose concentration keeps constant, except in 5th order rivers. Increasing elemental concentration downflow is mainly due to silicate weathering and carbonates dissolution. The latter is probably associated with atmospheric dust and disseminated calcite in regolith and soils from the study area. Mountainous rivers and streams are diluted due to the short water-rock contact time and also because soils and sediment accumulations are shallow. In the study area, total dissolved solids (TDS) vary between 10 and 60 mg l-1, which implies a shared atmospheric and weathering control (Gibbs, 1970). River waters draining crystalline rocks show electrical conductivity values from